2017
DOI: 10.20472/bm.2017.5.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Enterprises and Distance: Exploring Opportunities and Challenges Involved in Practicing CSR in Host-Countries

Abstract: Abstract:This study explores how multinational enterprises (MNEs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recently, researchers have begun to elucidate the role of distance on firms' stance on CSR [39]. Some scholars confirmed that participating in CSR activities in the host country can alleviate the impact of distance on enterprises [40].…”
Section: Theoretical Background 21 Csr and Distancementioning
confidence: 99%
“…Recently, researchers have begun to elucidate the role of distance on firms' stance on CSR [39]. Some scholars confirmed that participating in CSR activities in the host country can alleviate the impact of distance on enterprises [40].…”
Section: Theoretical Background 21 Csr and Distancementioning
confidence: 99%
“…Volunteers advocate cultural interaction and understanding between hosts and guests over a longer period of time, while both the volunteers and locals have the power to be assured of their identities and relations with each other (McGehee, 2002). Although tourism has the function of poverty-alleviation (Ball, 2009;Amos and Swuah, 2017), it is controversial in what degree tourism can improve the economy and in what circumstances it will do. Volunteer tourism presents the principal motivation of taking people to poor parts of the world to make some contribution (Crossley, 2012).…”
Section: Volunteer Tourism and The Destinationsmentioning
confidence: 99%